Faktor determinan kepuasan kerja karyawan PT Sarana Scientifa Systemindo - Fanillah, Nesya; Farida, Farida (Universitas Indraprasta PGRI, 2023)
In this statistical analysis, the researcher used the SPSS ver 25.0 For Windows program. Data processing was carried out with the SPSS (Statistical Package for The Social Science) ver 25.0programsm with a population of 50 employees. The technique for determining the sample in this study uses a saturated sampling technique or census sampling, in which all members of the population are sampled. Adjusted R Square with multiple determinations is 61.3% and the remaining 38.7% is the contribution of other factors. For multiple linear regression values, Y = 0.228 + 0.362 X1 + 0.258 X2 + 0.369 X3 and the F test = 5%. The F-count value is 26.826 and F-table is 2.81, meaning the F-count > F-table, it can be said that there is a significant influence between cultures. organization, leadership, and compensation for employee job satisfaction of PT Sarana Scientifa Systemindo